RETRACTED: Pengelolaan Sampah Plastik Daerah Kepulauan Di Siberut Selatan Mentawai - Sudiar, Nofi Yendri; Asrizal, Asrizal; Razi, Pakhur; Gautama, Muhammad Isa (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2022)
RETRACTION TO:Sudiar, N. Y. (2022). Pengelolaan Sampah Plastik Daerah Kepulauan Di Siberut Selatan Mentawai. Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 22(2), 224-233. (doi: https://doi.org/10.24036/sb.02330This article has been retracted by the Publisher based on the following reason:The Editor of Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat obtains requests from the author for changes authors to the Incorrect author/contributor list (i.e., an eligible author has been omitted or someone who does not meet the authorship criteria has been included).